2018
DOI: 10.1093/eurheartj/sux035
|View full text |Cite
|
Sign up to set email alerts
|

Landiolol for rate control management of atrial fibrillation in patients with cardiac dysfunction

Abstract: Atrial fibrillation (AFib) is frequently associated with heart failure. Guidelines for AFib management have been recently updated and include an algorithm for acute heart rate control based on left ventricular ejection fraction and haemodynamics. Landiolol is an injectable ultra-short beta-blocker with very high beta-1 selectivity, listed in Japanese Guidelines for AFib management as potential option for rate control of patient with heart failure. Landiolol is now available in Europe with indication of control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…However, it may be important to characterize LV systolic function when initiating landiolol treatment [ 19 ]. Wada et al reported that an extremely low LVEF (< 25%) was a predictor of inadequate heart-rate lowering during landiolol therapy and was associated with the development of adverse events, such as hypotension [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it may be important to characterize LV systolic function when initiating landiolol treatment [ 19 ]. Wada et al reported that an extremely low LVEF (< 25%) was a predictor of inadequate heart-rate lowering during landiolol therapy and was associated with the development of adverse events, such as hypotension [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic properties of landiolol indicate that it is rapidly metabolized in plasma by pseudocholinesterase and has a very short elimination half-life of approximately 4 min [ 15 , 16 ]. Recently, landiolol has been reported to be useful for heart rate control in AF patients with HF or reduced left ventricular (LV) systolic dysfunction [ 19 ]. However, the effect of landiolol on ATAs complicated with acute decompensated HF (ADHF) has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Rate control with landiolol in HFrEF and AF Landiolol is not widely used for those with cardiac dysfunction in Europe thus far, although such an indication is receiving great concern. 27,28 In the current European Society of Cardiology guideline published in 2016, 29 the smallest dose of β-blocker is recommended as a first-line to achieve rate control in case of atrial fibrillation with cardiac dysfunction, followed by amiodarone and digoxin.…”
Section: Post-j-land Study Guidelinesmentioning
confidence: 99%
“…Esant sumažėjusiai KS IF (<40 proc. ), rekomenduojama landiololio dozė neturėtų viršyti 10 µg/kg/ minutę [20]. Vieno centro studijoje nustatyta, jog landiololio skyrimas pacientams su ŪDŠN pagerino ligos baigtį ir sumažino pakartotinių hospitalizacijų kiekį [14].…”
Section: Rezultatai Ir Jų Aptarimasunclassified